UBQLN2 mutation causing heterogeneous X‐linked dominant neurodegeneration. Issue 5 (9th May 2014) - Fahed, Akl C.; McDonough, Barbara; Gouvion, Cynthia M.; Newell, Kathy L.; Dure, Leon S.; Bebin, Martina; Bick, Alexander G.; Seidman, Jonathan G.; Harter, Donald H.; Seidman, Christine E.
<x xml:space="preserve">Abstract</x> We report a 5‐generation family with phenotypically diverse neurodegenerative disease including relentlessly progressive choreoathetoid movements, dysarthria, dysphagia, spastic paralysis, and behavioral dementia in descendants of a 67‐year‐old woman with amyotrophic lateral sclerosis. Disease onset varied with gender, occurring in male children and adult women. Exome sequence analyses revealed a novel mutation (c.1490C>T, p.P497L) in the ubiquilin‐2 gene (UBQLN2) with X‐linked inheritance in all studied affected individuals. As ubiquilin‐2–positive inclusions were identified in brain, we suggest that mutant peptide predisposes to protein misfolding and accumulation. Our findings expand the spectrum of neurodegenerative phenotypes caused by UBQLN2 mutations. ANN NEUROL 2014;75:793–798